Telaah Ontologis Klasifikasi Ilmu Hadis: Dirāyah dan Riwāyah sebagai Basis Taksonomi - Multajam, Muhammad Dikri (Journal of Hadith Studies, 2022)
This paper explains the origin and development of the concept of the division of hadith science into Dirāyah and Riwāyah and its relevance to the division of hadith science in the context of modern hadith studies. The author addresses the following issue: first, what is the origin and development of the concept of the division of hadith science into Dirāyah and Riwāyah? Second, what is the methodology used in each branch of hadith science? Third, what is the relevance and role of the division of hadith science in the context of modern hadith studies? This paper is a literature study that uses qualitative research methods based on literature research with a descriptive-analytical approach. The primary sources of this paper are taken from the books of ulumul hadith, which are complemented by secondary sources in the form of other relevant literature. This research concludes that Hadith Science is divided into two main branches: Dirāyah Science and Riwāyah Science. The science of Dirāyah focuses on critical analysis of hadith, including two assessments: first, the sanad (chain of narration), including connectedness, trustworthiness, and safety from irregularities and defects. Secondly, the matan (content of the hadith) focuses on compatibility with the Qur'an, irregularities in wording, meaning, and foreign terms. Meanwhile, Riwāyah Science focuses on the collection, writing, and narration of hadith. Through methods of collection from companions, systematic writing, filtering of hadith, and preservation through memorization and recording, this science ensures the authenticity and preservation of hadith. These two branches complement each other in ensuring that the hadith received and understood by Muslims are sahih and have high scientific integrity.